The Entrepreneurship Interest of XI Grade Marketing Students in Vocational Highschools in Semarang - Farida, Sifa; Thomas, Partono; Prihandono, Dorodjatun (Universitas Negeri Semarang, 2020)
One way to reduce the number of unemployment and improve the Indonesian economy is by increasing entrepreneurship interest of the younger generation. This study aims to analyze and identify entrepreneurship interests of XI Grade Marketing students in Public Vocational Schools in Semarang. This study uses a quantitative approach. The variables in this study are entrepreneurship interest (Y), entrepreneurship attitude (X1), subjective norms (X2), self-efficacy (X3) and Entrepreneurship Learning (M). The population of the study was 215 students and the sample was 140 students. The sampling technique uses proportional random sampling. The results of this study indicate that there is a direct effect of entrepreneurship attitude on entrepreneurship interest, subjective norms on entrepreneurship interest and self-efficacy on entrepreneurship interest. Entrepreneurship learning moderates the influence of entrepreneurship attitude on entrepreneurship interest indirectly. While entrepreneurship learning does not moderate the influence of subjective norms and self-efficacy on entrepreneurship interest.